Effect of different CaSO4 contents on CaSiO3‐CaSO4 porous composite bone scaffolds by 3D gel‐printing. Issue 6 (26th July 2020) - Shao, Huiping; Yu, Xinding; Zhang, Zhinan; Lin, Tao; Peng, Jiang; Wang, Aiyuan; Liu, Shuwen; Zhao, Manjian
Abstract: Porous CaSiO3 ‐CaSO4 composite scaffolds were successfully prepared by 3D gel‐printing (3DGP) technology in this study. In order to further improve the degradation performance of pure CaSiO3 scaffolds, the effect of different CaSO4 doping contents on CaSiO3 ‐CaSO4 composite scaffolds was studied. The results show that when the porous composite scaffolds were placed in simulated body fluid (SBF) for 5 weeks, the weight loss rate was 2.41% (CaSiO3 ‐1%CaSO4 ), 3.97% (CaSiO3 ‐3%CaSO4 ), 4.18% (CaSiO3 ‐5%CaSO4 ), 6.87% (CaSiO3 ‐7%CaSO4 ), and 12.93% (CaSiO3 ‐9%CaSO4 ), respectively, which could be concluded that CaSO4 doping has a significant effect on improving the biodegradability of CaSiO3 scaffolds. And CaSO4 doping can also effectively improve the compressive strength of composite scaffolds and that of CaSiO3 ‐3%CaSO4 composite scaffolds was tested as 54.67 MPa, and the shrinkage rate of porous composite scaffolds was nearly 11.4%, which meets the application requirements of bone repairing engineering.